Optimization of Aloe vera as a Natural Plant Growth Regulator to Enhance the Growth of Dendrobium Orchid ‘Arif’ - Imarotul Umamah; Endah Rita Sulistya Dewi; Praptining Rahayu (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the effects of different concentrations of Aloe vera as a natural plant growth regulator (PGR) on the growth of Dendrobium ‘Arif’ orchids. The observed parameters included root length, stem height, and shoot height as indicators of vegetative growth. The experiment employed a completely randomized design (CRD) with five treatments: a control (0%) and Aloe vera extract at concentrations of 1%, 3%, 5%, and 7%, each with three replicates. Data were analyzed using one-way ANOVA, followed by Tukey’s HSD test at a 5% significance level. The results showed that Aloe vera had a significant effect on stem height (F = 2.712; p = 0.043) and root length (F = 5.896; p = 0.001), but no significant effect on shoot height (F = 0.359; p = 0.836). The 5% concentration produced the highest mean stem height (8.00 cm), exceeding that of the control (6.94 cm), 1% (6.89 cm), 3% (6.39 cm), and 7% (6.83 cm). For root length, the 5% concentration also yielded the highest value (8.98 cm), compared with 1% (7.76 cm), the control (6.40 cm), 7% (5.95 cm), and 3% (4.56 cm), and differed significantly according to Tukey’s HSD test. The non-significant response in shoot height suggests differences in physiological sensitivity among plant organs, with roots and stems being more responsive to auxins and gibberellins present in Aloe vera. Overall, Aloe vera extract shows potential as a natural PGR to support the vegetative growth of Dendrobium orchids, particularly in root and stem development.